A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
Question 6 of the Unit 1 exam supposes f satisfies:
f(x+y) = f(x) + f(y) + x^2y + xy^2
It also supposes (A) the limit of f(x)/x as x nears 0 is 1. It says to evaluate f(0).
The solutions says that if A, then (B) the limit of f(x) as x nears 0 is 0. I see that given B, f(0) = 0, but how does A get you to B?
It seems more obvious that since
f(0+0) = f(0) + f(0) + 0^2*0 + 0*0^2,
it has to be that f(0) = f(0) + f(0),
but then f(0) = 0.
It is clear how to go on from here, can someone explain the connection between A and B?
anonymous
 one year ago
Question 6 of the Unit 1 exam supposes f satisfies: f(x+y) = f(x) + f(y) + x^2y + xy^2 It also supposes (A) the limit of f(x)/x as x nears 0 is 1. It says to evaluate f(0). The solutions says that if A, then (B) the limit of f(x) as x nears 0 is 0. I see that given B, f(0) = 0, but how does A get you to B? It seems more obvious that since f(0+0) = f(0) + f(0) + 0^2*0 + 0*0^2, it has to be that f(0) = f(0) + f(0), but then f(0) = 0. It is clear how to go on from here, can someone explain the connection between A and B?

This Question is Closed

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Ah, I see.... Given lim [f(x)/x] (x>0) = 1: Then: ln(lim (x>0) [f(x)/x]) = 0. Then: lim (x>0) [ln f(x)  ln x] = 0 Then: lim (x>0) [ln f(x)] = lim (x>0) [ln x] Then: ln [lim (x>0) f(x)] = ln [lim (x>0) x] Then: e^(ln [lim (x>0) f(x)]) = e^(ln [lim (x>0) x]) Then: lim (x>0) f(x) = lim (x>0) x Since lim (x>0) x = 0, so lim (x>0) f(x) = 0. Needs most of the tricks....

phi
 one year ago
Best ResponseYou've already chosen the best response.1yes, your way works. another way is start with \[ \lim_{x\rightarrow 0} \frac{f(x)}{x} = 1 \] being pedantic we can also take the limit of the right side \[ \lim_{x\rightarrow 0} \frac{f(x)}{x} = \lim_{x\rightarrow 0}1 \] as long as x is not zero we can multiply both sides by x \[ \lim_{x\rightarrow 0} f(x) = \lim_{x\rightarrow 0}x\] as x goes to zero, write this as \[ f(0)= 0 \]

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Interesting. I knew that \[\lim_{x \rightarrow 0}c f(x) = c \lim_{x \rightarrow 0} f(x)\] (cool editor) but I hadn't suspected that c could be x. Learned another trick today....

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0After some time, that is a cool approach. Thanks for the lesson. That's why I looked for this place.

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0phi, I just realized that *that* wasn't what you did, but what you did was interesting too.

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0The key step is: lim(x>0) x * lim(x>0) f(x)/x = lim(x>0) x * lim(x>0) 1, and so: lim(x>0) x * f(x)/x = lim(x>0) x * 1, et cetera.
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.